1987
DOI: 10.1038/bjc.1987.148
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of tumour versus normal tissue glutathione by buthionine sulfoximine

Abstract: Summary We have investigated in detail the effects of buthionine sulfoximine (BSO), a selective glutathione (GSH) depleting agent, on the GSH contents of a number of normal tissues and three experimental tumours in mice. Significant variations in the rate and degree of GSH depletion and recovery were observed among the normal tissues. Following a dose of 2.5 mmol kg-1 BSO, GSH nadirs were reached by approximately 5 h for the liver and kidney, 8 h for the lung and bone marrow, 12 h for red blood cells (RBCs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
44
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 11 publications
7
44
0
Order By: Relevance
“…It is the most abundant intracellular non-protein thiol and the cellular content amounts to 0.5-10 nmol 1' (Meister & Anderson, 1983;Dusre et al, 1989). It has been demonstrated that bone marrow of both animals and healthy humans contain a low level of intracellular GSH as compared to other normal tissues (Somfai-Relle et al, 1984a;Jaeschke & Wendel, 1985;Tsutsui et al, 1986;Lee et al, 1987;Smaaland et al, 1991b), and this may contribute to the reduced tolerance of bone marrow cells towards cytotoxic drugs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is the most abundant intracellular non-protein thiol and the cellular content amounts to 0.5-10 nmol 1' (Meister & Anderson, 1983;Dusre et al, 1989). It has been demonstrated that bone marrow of both animals and healthy humans contain a low level of intracellular GSH as compared to other normal tissues (Somfai-Relle et al, 1984a;Jaeschke & Wendel, 1985;Tsutsui et al, 1986;Lee et al, 1987;Smaaland et al, 1991b), and this may contribute to the reduced tolerance of bone marrow cells towards cytotoxic drugs.…”
mentioning
confidence: 99%
“…Glutathione (GSH), a cystein-containing tripeptide, has been assigned an important role in the cellular defence against free radicals and reactive oxygen intermediates, as well as in detoxification processes and in the protection of the cell against radiation damage (Dethmers & Meister, 1981;Bump et al, 1982;Meister, 1983;Biaglow et al, 1983;Lee et al, 1987;Friedman et al, 1989). It is the most abundant intracellular non-protein thiol and the cellular content amounts to 0.5-10 nmol 1' (Meister & Anderson, 1983;Dusre et al, 1989).…”
mentioning
confidence: 99%
“…Single cell suspensions from 14 human cancers were prepared by 23-gauge needle aspiration or mechanical disaggregation of surgical specimens, stained using mBCI and examined by flow cytometry. There was a wide range in individual cell fluorescence, which in contrast to EMT6 cells was not strongly correlated with (Ozols et al, 1987;Lee et al, 1987;Skapek et al, 1988 Clinical samples A total of 14 clinical samples were examined. Seven of these were obtained by 23 gauge needle aspiration from patients who gave verbal informed consent for the procedure, one consisted of peripheral blood lymphoblasts separated by density-gradient centrifugation from a patient with end-stage T-cell acute lymphoblastic leukaemia, and the remainder were fresh surgical specimens which were mechanically disaggregated using crossed scalpel blades.…”
mentioning
confidence: 99%
“…Glutathione is an abundant molecule in cells, cytoplasmic concentrations being typically in the millimolar range, and there is increasing evidence that elevated tumour cell GSH or glutathione-S-transferase activity could be an important cause of radiation and alkylating agent resistance in cancer patients. In particular, resistant cell lines often show an elevated GSH content, while pre-treatment of tumourbearing animals with buthionine sulphoximine (BSO), which reduces GSH content by blocking gamma-glutamyl-cysteine synthetase, can improve the therapeutic index of alkylating agents (Ozols et al, 1987;Lee et al, 1987;Skapek et al, 1988 Tietze (1969). This involves reduction of the aromatic disulphide 5,5'-dithiobis(2-nitrobenzoic acid) (DTNB) to the chromogenic TNB by GSH, which is oxidised to its disulphide-linked dimeric form GSSG.…”
mentioning
confidence: 99%
“…However, preclinical data in mice indicated that normal tissue also experienced GSH depletion when BSO was administered [64]. After a single bolus dose, mice bearing tumors were reported to show GSH depletion by 5 h in the liver (74% depletion) and kidney (80%), by 8 h in the lung (40%) and bone marrow (83%), by 12 h for red blood cells (13%) and by 24 h for the heart (54%).…”
Section: Bso: Animal Studies and Clinical Trialsmentioning
confidence: 99%